Analysis of Residual Stress And Strain on The Formation of Workpiece Based Ansys 12.1 - Sonny Prayogi; Zulkarnain . (Universitas Sriwijaya, 2015)
Machining process to produce plastic deformation on the workpiece. Plastic deformation during the machining process are formed by friction against the cutting tools to workpieces generate furious. During the deformation process appearance residual stress on the surface which can affect the fatigue resistance, fracture strength, and corrosion. Failure in the component structure is not only due to external forces, residual stress is an important parameter in this case. The purpose of this study to analyze the residual stresses that occur on the workpiece from turning process. In the analysis performed using the Finite Element Method (FEM) with the software to obtain the desired results by entering input data including modeling of cutting tools and the workpiece. The result is a visual overview of the residual stress in the workpiece and areas of plastically deformed as a result of feeding from the cutting tools motion. 2D visual modeling using the software Ansys 12.1 with three comparison rake angle 50, 100.150 to determine the result of the residual stress on the surface of the workpiece.